2019
DOI: 10.3390/polym11020347
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printable PP/SEBS Thermoplastic Elastomeric Blends: Preparation and Properties

Abstract: Currently, material extrusion 3D printing (ME3DP) based on fused deposition modeling (FDM) is considered a highly adaptable and efficient additive manufacturing technique to develop components with complex geometries using computer-aided design. While the 3D printing process for a number of thermoplastic materials using FDM technology has been well demonstrated, there still exists a significant challenge to develop new polymeric materials compatible with ME3DP. The present work reports the development of ME3DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 27 publications
(36 reference statements)
0
88
0
2
Order By: Relevance
“…However, with FFF printing, defects, By using printers with dual or multiple extrusion nozzles, multicolored or multiple material parts can be produced. Simultaneous 3D printing of multiple materials enables integration of different properties (e.g., flexibility, folding, deployment, shape memory, and electric conductivity) into intricate products in a single manufacturing process [15][16][17][18]. Additionally, a wide range of polymers used for FFF nowadays can be recycled, and the nonmelted material (metal and polymer) from different AM processes can be reused [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with FFF printing, defects, By using printers with dual or multiple extrusion nozzles, multicolored or multiple material parts can be produced. Simultaneous 3D printing of multiple materials enables integration of different properties (e.g., flexibility, folding, deployment, shape memory, and electric conductivity) into intricate products in a single manufacturing process [15][16][17][18]. Additionally, a wide range of polymers used for FFF nowadays can be recycled, and the nonmelted material (metal and polymer) from different AM processes can be reused [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Figures 9,12,14,and 16 show the effect of interaction (quadratic model) of process parameters on each process responses individually. Analysis of variance (ANOVA) was conducted to identify the most significant terms affecting the response values.…”
mentioning
confidence: 99%
“…Many researchers have been devoted to developing new materials for FDM, such as polypropylene (PP), 11 poly(vinyl alcohol) (PVA), 12 thermoplastic polyurethane (S‐TPU), 13 and their composites 14 . Polymer blending is an effective and economic method to achieve the specific required properties like better processability and printability 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SEBS can be easily processed and modified. Due to the compatibility, it is widely used in hybridization with many different types of polymers such as copolymer coatings, adhesives, sealants, and engineering plastics . In addition, scientific studies have shown that increased concentration of SEBS in hybrid polymer blends could improve breaking elongation and interfacial adhesion, which allows developing the properties of ductility, toughness, and impact‐resistance …”
Section: Introductionmentioning
confidence: 99%